Arterial spin labeling magnetic resonance imaging quantifies tissue perfusion around foot ulcers - Pantoja, Joe Luis; Ali, Fadil; Baril, Donald T.; Farley, Steven M.; Boynton, Scott; Finn, J. Paul; Hu, Peng; Lawrence, Peter F. (Journal of vascular surgery cases and innovative techniques, 2022)
Tools that quantify tissue perfusion of the foot are deficient, contributing to the uncertainty in predicting ulcer healing potential. This pilot study aims to quantify peri-wound foot perfusion at various tissue depths using a novel application of pseudo-continuous arterial spin labeling magnetic resonance imaging. Ten diabetic patients with neuropathic wounds and 20 healthy volunteers without wounds were recruited. Wounds were graded according to the Wound, Ischemia, Foot Infection (WIfI) system. All subjects underwent a noncontrasted ASL MRI of the foot for perfusion measurements. For healthy volunteers, perfusion was compared at rest and during sustained toe flexion between four regions: lateral plantar, medial plantar, lateral calcaneal, and medial calcaneal. Evaluations of diabetic volunteers compared perfusion between four zones: wound, near border, far border, and remote. Remote zone perfusion in diabetics was compared with perfusion in the plantar foot of healthy volunteers. There were 11 wounds, which were located over the metatarsal heads in five, the stump of a transmetatarsal amputation in three, the heel in two, and the mid foot in one. The median WIfI stage was 2. One patient had a WIfI ischemia grade of 1; the remaining patients’ grades were 0. The mean ankle-brachial index was 1.0 ± 0.3. There were two patients with a WIfI foot infection grade of 1; the remaining patients’ grades were 0. In healthy volunteers, plantar foot perfusion with sustained toe flexion was 43.9 ± 1.7 mL/100g/min and significantly higher than perfusion at rest (27.3 ± 2.7 mL/100g/min; P < .001). In diabetic patients, perfusion at the wound, near border, far border, and remote regions was 96.1 ± 10.7, 92.7 ± 9.4, 73.4 ± 8.2, and 62.8 ± 2.7 mL/100g/min. Although this perfusion pattern persisted throughout the depth of the wound, perfusion decreased with tissue depth. In the near border, perfusion at 20% of the wound depth was 124.0 ± 35.6 mL/100g/min and 69.9 ± 10.1 mL/100g/min at 100% (P = .006). Lastly, remote perfusion in diabetics was 2.3 times the plantar perfusion in healthy volunteers (27.3 ± 2.7 mL/100g/min; P < .001). The pattern of resting tissue perfusion around nonischemic diabetic foot ulcers was successfully quantified with arterial spin labeling magnetic resonance imaging. Diabetic patients with wounds were hyperemic compared with healthy volunteers. There was a 1.5-fold increase in peri-wound tissue perfusion relative to the rest of the foot. This study is the first step in developing a tool to assess the perfusion deficit in ischemic wounds.